PERBANDINGAN METODE SIMPLE QUEUE DAN QUEUE TREE DALAM OPTIMALISASI MANAJEMEN BANDWIDTH - Nafis Naufal Anwari; Puwantoro .; Tesa Nur Padilah (STMIK Dian Cipta Cendikia Kotabumi, 2022)
The internet is currently very much needed because of the increasing number of users, many people are dependent on the internet because this information technology is very fast. In this case, it has a huge impact on the need for the provision of very efficient internet services. One technology that is becoming a trend in computer networks, namely wireless computer networks (wireless local area networka / WLAN). This technology is the development of local area network technology that allows efficiency in the implementation and development of computer networks that can increase user mobility and computer network technology using cable media. Bandwidth management is a way to manage the internet network for even distribution of bandwidth usage even though many network users use the simple queue and queue tree method, one method for doing a bandwidth management, in this simple queue and queue tree there are bandwidth management settings and can add bandwidth size every larger client, this research methodology uses qualitative research results. The results showed that the results of the comparison of two simple queue and queue tree methods were optimal enough to be used in cybercomnet bandwidth management.